Guidelines for enforcing laws regarding sexual harassment - Vorawee, Jugkrit; Phongsakonphanit, Mathurin; Abhirathanarath, Athiwat (Huachiew Chalermprakiet Law Journal, 2024)
Sexual harassment is increasing in Thai society and many other countries, affecting daily life and work responsibilities. It takes various forms, including visual harassment, verbal harassment, physical harassment through touching, and online harassment. There are multiple versions of laws aimed at addressing such offenses, but enforcing these laws is challenging due to insufficient evidence to convince the court of the offender’s guilt. This stems from the limitations faced by the victims in accessing the justice process. There is also a lack of preparedness among personnel involved in the investigation, and foreign labor groups face obstacles in accessing language assistance. Cases of sexual harassment that do not reach the level of rape or coercion are often considered minor, and the punishment does not serve as a deterrent. It is necessary to further amend the laws to have appropriate penalties for such offenses. However, if the laws are not amended, it is important to consider sentencing according to the existing applicable laws, such as imposing imprisonment without waiting for criminal sentences or considering both imprisonment and fines. This is to compensate the victims and create a sense of fear and deterrence, so that individuals are less likely to commit such offenses again. This can be another way to address the issue of sexual harassment.